2018
DOI: 10.1159/000494328
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnoea in Children and Adolescents with Ehlers-Danlos Syndrome

Abstract: Background: In Ehlers-Danlos syndrome (EDS), a group of monogenic disorders affecting connective tissues, obstructive sleep apnoea (OSA) is highly prevalent in adults. The prevalence of OSA in children with EDS is unknown. Objectives: This prospective cross-sectional study aimed at determining the prevalence of OSA in paediatric EDS patients. Methods: Children with EDS (n = 24) were recruited from the Children’s Hospital Zurich and matched to healthy controls. Participants completed home respiratory polygraphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The discreetly high incidence of chronic fatigue observed in our cEDS cohort is in line with previous observations that emphasized that in EDS this issue is more common than in the general population and likely contributes to the patients’ functional impairment, psychological distress, and decreased QoL [ 86 – 89 ]. Like in the general population, in cEDS fatigue is multifactorial with contributing factors including articular pain, headache, sleep disturbance, and abnormally low blood pressure often associated with postural orthostatic tachycardia syndrome (POTS) or neurally mediated hypotension (NMH), nutritional deficiency, medications, and/or allergies (present in 32% of our patients) [ 80 , 81 , 87 , 90 95 ]. Cerebrospinal fluid leak, which has been reported in cEDS as a cause of postural hypotension and headache [ 96 ], was not diagnosed in our cohort (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The discreetly high incidence of chronic fatigue observed in our cEDS cohort is in line with previous observations that emphasized that in EDS this issue is more common than in the general population and likely contributes to the patients’ functional impairment, psychological distress, and decreased QoL [ 86 – 89 ]. Like in the general population, in cEDS fatigue is multifactorial with contributing factors including articular pain, headache, sleep disturbance, and abnormally low blood pressure often associated with postural orthostatic tachycardia syndrome (POTS) or neurally mediated hypotension (NMH), nutritional deficiency, medications, and/or allergies (present in 32% of our patients) [ 80 , 81 , 87 , 90 95 ]. Cerebrospinal fluid leak, which has been reported in cEDS as a cause of postural hypotension and headache [ 96 ], was not diagnosed in our cohort (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…[203][204][205] In 26% to 42% of children and 32% of adults, obstructive sleep apnea has been reported. 203,206,207 Psychological manifestations of hEDS have been focused mainly on anxiety and depression, which have both been described in hEDS/JHS patient population. [208][209][210] It is unknown whether these are a result of living with a chronic disorder and pain, or if there is another explanation for the relationship.…”
Section: Sleep Fatigue Pain and Psychological Impactmentioning
confidence: 99%
“…Sleep problems such as insomnia and poor sleep quality are common in children and adults with hEDS 203‐205 . In 26% to 42% of children and 32% of adults, obstructive sleep apnea has been reported 203,206,207 . Psychological manifestations of hEDS have been focused mainly on anxiety and depression, which have both been described in hEDS/JHS patient population 208‐210 .…”
Section: Phenotypementioning
confidence: 99%
“…These findings are in line with another study (Muriello et al, 2018) that found that both pain and poor sleep quality negatively impacted the quality of life of these patients. Stoberl et al (2019) studied OSA in children and adolescents with EDS and found an estimated prevalence of 42% and concluded that OSA is highly prevalent in children with EDS but is underestimated which increased the disease burden. Domany and his group (Domany et al, 2018) also studied sleep disorder in pediatric populations with EDS and not surprisingly, results showed a high prevalence of OSA but also insomnia, periodic limb movement disorder, and hypersomnia in EDS children.…”
Section: Sleep Disordersmentioning
confidence: 99%